MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI METODE PERMAINAN LOMPAT ANGKA UNTUK ANAK USIA 4-5 TAHUN DI RA DARUSSALAM SUMBERMANJING-MALANG - Zuhriyah, Aminatuz; Sari, Ratih Permata (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2019)
The process of early childhood learning is done by the technique of "learning as a play". Increasing the creativity of educators in creating innovations in learning. This study aims to improve the ability to recognize the symbol of numbers in children aged 4-5 years in RA Darussalam Sumberkembang Sumbermanjing-Malang. Classroom Action Research (Action Research) using two cycles is applied to children aged 4-5 years. Data collection techniques through observation, interviews, and documentation. The results of observations before the action show that the increase in the ability to recognize symbol numbers occurs starting from the pre-action, the first cycle to the second cycle. In pre-action, the percentage of recognizing number symbols in children reached 45.83%, in cycle I it reached 63.42% and in cycle II it reached 82.87%. Research can be concluded that the game method is very effective in improving aspects of development, especially in cognitive abilities through learning to recognize the number symbols for early childhood.